Pelaksanaan Pembelajaran Bernyanyi Secara Unisono Berdasarkan Kurikulum 2013 Edisi Revisi Di Kelas VII-2 SMP Negeri 3 Padang - Doni Febri; Tulus Handra Kadir; Harisnal Hadi (SENDRATASIK UNP, 2021)
This study aims to explore and describe the implementation of Culture and Arts instruction based on the revised 2013 curriculum of 2016 edition at SMP Negeri 3 Padang. This is a qualitative research using descriptive method. The research instrument was the researcher itself and was assisted by supporting instruments such as writing tools and cameras. The data were collected through literature study, observation, interview, and documentation. The data analysiswas conducted through collecting the data, describing the data, taking conclusion and making suggestions. The results showthat the unisono singing instruction conducted by teachers in class VII-2 of SMP Negeri 3 Padang has not gone well and had not met the targets of the learning objectives and the objectives of the revised 2013curriculum. This can be seen from the planning, implementation, and evaluation. Thereisnorelevancy between the lesson plans and those implemented by the teacher in the classroom. Teachers do not fully understand the concepts and techniques of singing unisono so that students do not understand the subject matter. The results of the unisono learning evaluation of students in class VII-2show that the highest score got only reached 87, the lowest score was 75, and 10 students did not reach the cut score.